Radio Astronomy Research in Malaysia: past, present and future - Abidin, Z.Z.; Ibrahim, Z.A. (2009)
This paper will report on the progress in the research field of radio astronomy in Malaysia and also in South-East Asia. Radio astronomy research can be said to have only started being done actively in Malaysia in 2005. Fundamental setup and some basic research were done in the early parts. Jupiter radio bursts as well as radio meteor counting were the first few projects. Currently a medium-sized radio telescope which was recently purchased is being used to undergo more advanced research such as observing spectrum of galaxy clusters in order to study Dark Matter. This paper will also report on the latest results on the survey of Radio Frequency Interference (RFI), which is currently done on chosen candidate sites in Malaysia in order to setup on it a large radio telescope in the future. The best site with the lowest averaged REI level is found at Langkawi (-100.33 dBm or 4.4 x 10(6) Jy). The author is the chair for the Radio Astronomy Working Group for the South-East Asia Astronomy Network (SEAAN) and the Malaysian team is very much an important part of this group. This group will eventually be a research hub for the global projects of the Global-Very Long Baseline Interferometer (Global-VLBI) and the Square Kilometre Array (SKA).